GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Direct ultrastructural validation of endocrine cell identity in zebrafish pancreatic islets - N. Schmitner; C. Deseife; A. Neumann; W. Salvenmoser; A. C. Seybold; R. A. Kimmel; D. Meyer (Cell and Tissue Research, 2026)
The zebrafish is widely used to study glucose homeostasis, diabetes, and endocrine cell plasticity, yet a definitive ultrastructural characterization of adult pancreatic endocrine cell types has remained incomplete. Here, we combined transmission electron microscopy with hormone-specific immunogold labeling to define the ultrastructural characteristics of the major endocrine cell populations in adult zebrafish pancreatic islets. Three principal endocrine cell types were distinguished based on secretory granule morphology, electron density, and intracellular organization. Glucagon-positive α-cells contained electron-dense granules with a characteristic halo and eccentric dense core, insulin-positive β-cells displayed larger moderately electron-dense granules, and somatostatin-positive δ-cells possessed smaller, predominantly electron-dense granules of heterogeneous shape. Immunogold labeling for glucagon, insulin, and somatostatin linked granule ultrastructure to endocrine cell identity. To independently validate β-cell assignment, we performed nitroreductase-mediated β-cell ablation in juvenile zebrafish and observed a marked depletion of cells containing the characteristic medium electron-dense granules. Comparative analysis indicates that zebrafish endocrine granule ultrastructure differs in several respects from mammalian islets and exhibits similarities to selected teleost species, highlighting evolutionary diversity in endocrine granule organization. This study provides a foundational ultrastructural reference for the three major endocrine cell types of the adult zebrafish endocrine pancreas and establishes criteria for identifying these populations in studies of pancreatic disease, regeneration, and cell plasticity while also identifying an additional unassigned endocrine population that warrants further characterization.

Initiating environmental microplastics analysis: A review and planning guide with practical insights from laboratory implementation - Erica R. Forgione; Catherine Ferry; Bridget Neumann; Kelly D. Good (Science of The Total Environment, 2026)

Correction to: Oxytocin Receptor Expression in Hair Follicle Stem Cells: A Promising Model for Biological and Therapeutic Discovery in Neuropsychiatric Disorders - Sareh Pandamooz; Mohammad Saied Salehi; Benjamin Jurek; Carl-Philipp Meinung; Negar Azarpira; Mehdi Dianatpour; Inga D. Neumann (Stem Cell Reviews and Reports, 2026)

Challenges in measuring the size and velocity of large raindrops: a comparison of selected methods - M. Beczek; M. Neumann; R. Mazur; D. Zumr; T. Dostal; A. Bieganowski (Journal of Hydrology, 2025)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Elevated alpha-1 antitrypsin and C-reactive protein: association on all-cause and cause-specific mortality in older adults - Cammie Tran; Hans G. Schneider; Que T. Lam; Johannes T. Neumann; Flavia Cicuttini; Chenglong Yu; Zhen Zhou; Mark R. Nelson; Andrew M. Tonkin; Daniel Clayton-Chubb; Sultana Monira Hussain; Peter D. Fransquet; et al. (GeroScience, 2025)

Phylogenetic characterization of Bifidobacterium kimbladii sp. nov., a novel species from the honey stomach of the honeybee Apis mellifera - M. Modesto; D. Scarafile; A. Vásquez; R. Pukall; M. Neumann-Schaal; S. Pascarelli; B. Sgorbati; M. Ancora; C. Cammà; P. Mattarelli; T.C. Olofsson (Systematic and Applied Microbiology, 2025)

Nitrogen isotope homogenization of dissolved ammonium with depth and 15N enrichment of ammonium during incorporation into expandable layer silicates in organic-rich marine sediment from Guaymas Basin, Gulf of California - Toshiro Yamanaka; Arisa Sakamoto; Kanon Kiyokawa; Jaeguk Jo; Yuji Onishi; Yoshihiro Kuwahara; Ji-Hoon Kim; Lucie C. Pastor; Andreas Teske; Daniel Lizarralde; Tobias W. Höfig; Ivano W. Aiello; et al. (Chemical Geology, 2024)

Mineralization kinetics of biosiliceous sediments in hot subseafloors - Ivano W. Aiello; Tobias W. Höfig; Armelle Riboulleau; Andreas P. Teske; Daniel Lizarralde; Jeanine L. Ash; Diana P. Bojanova; Martine D. Buatier; Virginia P. Edgcomb; Christophe Y. Galerne; Swanne Gontharet; Verena B. Heuer; et al. (Geochimica et Cosmochimica Acta, 2024)

Healthy environments for athleTes (HEAT): environmental conditions along a 90 km ultra-marathon event, South Africa - H. Havenga; D. Gharbi; N. Sewry; B. Language; F. H. Neumann; J. M. Finch; T. Hill; J. Boulter; E. Jordaan; S. J. Piketh; M. Schwellnus; R. P. Burger (International Journal of Biometeorology, 2024)
This paper provides an overview of the HEAT (Healthy Environments for AthleTes) project, which aims to understand the impact of environmental conditions on athlete health and performance during major sporting events such as long-distance running, cycling, and triathlons. In collaboration with the SAFER (Strategies to reduce Adverse medical events For the ExerciseR) initiative, the HEAT project carried out a field campaign at the 2022 Comrades Marathon in the KwaZulu-Natal province of South Africa. The measurement campaign deployed seven weather stations, seven PM 2.5 monitors and one spore trap along the 90 km route to capture spatially representative measurements of complex micro-climates, allergenic aerospora, and particulate matter exposure. The results indicate that runners were exposed to moderate risk heat stress conditions. Novel findings from this initial campaign shows elevated and potentially harmful PM 2.5 levels at spectator areas, possibly coinciding with small fire events around the race day festivities. Our findings show values PM 2.5 levels over the WHO 24-h guidelines at all stations, while 2000 µg/m 3 at two stations. However, the lack of an acute exposure standard means direct health impacts cannot be quantified in the context of a sport event. The HEAT project highlights important aspects of race day monitoring; regional scale climatology has an impact on the race day conditions, the microclimatic conditions (pollution and meteorology) are not necessarily captured by proximity instruments and direct environmental measurements are required to accurately capture conditions along the route.

Letter to the editor regarding Collard et al. (2023): “Persistence and mobility (defined as organic-carbon partitioning) do not correlate to the detection of substances found in surface and groundwater: Criticism of the regulatory concept of persistent and mobile substances” - Hans Peter H. Arp; Raoul Wolf; Sarah E. Hale; Sivani Baskaran; Juliane Glüge; Martin Scheringer; Xenia Trier; Ian T. Cousins; Harrie Timmer; Roberta Hofman-Caris; Anna Lennquist; André D. Bannink; et al. (Science of The Total Environment, 2024)

Proline and Silver Nitrate Promotes Multiple Shoot Induction from Mature Embryo and Shoot Tip Explants of Sorghum - B. D. Pawar; N. R. Markad; R. S. Wagh; M. Neumann; A. A. Kale; V. P. Chimote (Sugar Tech, 2023)

Oxytocin Receptor Expression in Hair Follicle Stem Cells: A Promising Model for Biological and Therapeutic Discovery in Neuropsychiatric Disorders - Sareh Pandamooz; Mohammad Saied Salehi; Benjamin Jurek; Carl-Philipp Meinung; Negar Azarpira; Mehdi Dianatpour; Inga D. Neumann (Stem Cell Reviews and Reports, 2023)

Evaluating the addition of radar with optical data for vegetation mapping in a montane region in Sri Lanka - W. D. K. V. Nandasena; Lars Brabyn; Silvia Serrao-Neumann (Journal of Mountain Science, 2023)

Melissopalynological investigations of seasonal honey samples from the Greater Kruger National Park, Savanna biome of South Africa - Nikiwe Ndlovu; Frank H. Neumann; Michelle D. Henley; Robin M. Cook; Chevonne Reynolds (Palynology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

New phylogenetic insights into the African catfish families Mochokidae and Austroglanididae - Frederic D. B. Schedel; Albert Chakona; Brian L. Sidlauskas; Michael O. Popoola; Nadine Usimesa Wingi; Dirk Neumann; Emmanuel J. W. M. N. Vreven; Ulrich K. Schliewen (Journal of Fish Biology, 2022)
Several hundred catfish species (order: Siluriformes) belonging to 11 families inhabit Africa, of which at least six families are endemic to the continent. Although four of those families are well‐known to belong to the ‘Big‐Africa clade’, no previous study has addressed the phylogenetic placement of the endemic African catfish family Austroglanididae in a comprehensive framework with molecular data. Furthermore, interrelationships within the ‘Big‐Africa clade’, including the most diverse family Mochokidae, remain unclear. This study was therefore designed to help reconstruct inter‐ and intrarelationships of all currently valid mochokid genera, to infer their position within the ‘Big Africa clade’ and to establish a first molecular phylogenetic hypothesis of the relationships of the enigmatic Austroglanididae within the Siluriformes. We assembled a comprehensive mitogenomic dataset comprising all protein coding genes and representing almost all recognized catfish families ( N = 33 of 39) with carefully selected species ( N = 239). We recovered the monophyly of the previously identified multifamily clades ‘Big Asia’ and ‘Big Africa’ and determined Austroglanididae to be closely related to Pangasiidae, Ictaluroidea and Ariidae. Mochokidae was recovered as the sister group to a clade encompassing Auchenoglanididae, Claroteidae, Malapteruridae and the African Schilbeidae, albeit with low statistical support. The two mochokid subfamilies Mochokinae and Chiloglanidinae as well as the chiloglanid tribe Atopochilini were recovered as reciprocally monophyletic. The genus Acanthocleithron forms the sister group of all remaining Mochokinae, although with low support. The genus Atopodontus is the sister group of all remaining Atopochilini. In contrast to morphological reconstructions, the monophyly of the genus Chiloglanis was strongly supported in our analysis, with Chiloglanis macropterus nested within a Chiloglanis sublineage encompassing only other taxa from the Congo drainage. This is an important result because the phylogenetic relationships of C. macropterus have been controversial in the past, and because we and other researchers assumed that this species would be resolved as sister to most or all other members of Chiloglanis . The apparent paraphyly of Synodontis with respect to Microsynodontis provided an additional surprise, with Synodontis punu turning out to be the sister group of the latter genus.

Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2022)
Key message We present a comprehensive survey of cytogenetic and genomic diversity of the GGA t A t genepool of wheat, thereby unlocking these plant genetic resources for wheat improvement. Abstract Wheat yields are stagnating around the world and new sources of genes for resistance or tolerances to abiotic traits are required. In this context, the tetraploid wheat wild relatives are among the key candidates for wheat improvement. Despite its potential huge value for wheat breeding, the tetraploid GGA t A t genepool is largely neglected. Understanding the population structure, native distribution range, intraspecific variation of the entire tetraploid GGA t A t genepool and its domestication history would further its use for wheat improvement. The paper provides the first comprehensive survey of genomic and cytogenetic diversity sampling the full breadth and depth of the tetraploid GGA t A t genepool. According to the results obtained, the extant GGA t A t genepool consists of three distinct lineages. We provide detailed insights into the cytogenetic composition of GGA t A t wheats, revealed group- and population-specific markers and show that chromosomal rearrangements play an important role in intraspecific diversity of T. araraticum . The origin and domestication history of the GGA t A t lineages is discussed in the context of state-of-the-art archaeobotanical finds. We shed new light on the complex evolutionary history of the GGA t A t wheat genepool and provide the basis for an increased use of the GGA t A t wheat genepool for wheat improvement. The findings have implications for our understanding of the origins of agriculture in southwest Asia.

Correction to: Coastal flood risk within a peri‑urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2022)

Cardiovascular risk prediction in healthy older people - Johannes T. Neumann; Le T. P. Thao; Emily Callander; Enayet Chowdhury; Jeff D. Williamson; Mark R. Nelson; Geoffrey Donnan; Robyn L. Woods; Christopher M. Reid; Katrina K. Poppe; Rod Jackson; Andrew M. Tonkin; et al. (GeroScience, 2022)
Identification of individuals with increased risk of major adverse cardiovascular events (MACE) is important. However, algorithms specific to the elderly are lacking. Data were analysed from a randomised trial involving 18,548 participants ≥ 70 years old (mean age 75.4 years), without prior cardiovascular disease events, dementia or physical disability. MACE included coronary heart disease death, fatal or nonfatal ischaemic stroke or myocardial infarction. Potential predictors tested were based on prior evidence and using a machine-learning approach. Cox regression analyses were used to calculate 5-year predicted risk, and discrimination evaluated from receiver operating characteristic curves. Calibration was also assessed, and the findings internally validated using bootstrapping. External validation was performed in 25,138 healthy, elderly individuals in the primary care environment. During median follow-up of 4.7 years, 594 MACE occurred. Predictors in the final model included age, sex, smoking, systolic blood pressure, high-density lipoprotein cholesterol (HDL-c), non-HDL-c, serum creatinine, diabetes and intake of antihypertensive agents. With variable selection based on machine-learning, age, sex and creatinine were the most important predictors. The final model resulted in an area under the curve (AUC) of 68.1 (95% confidence intervals 65.9; 70.4). The model had an AUC of 67.5 in internal and 64.2 in external validation. The model rank-ordered risk well but underestimated absolute risk in the external validation cohort. A model predicting incident MACE in healthy, elderly individuals includes well-recognised, potentially reversible risk factors and notably, renal function. Calibration would be necessary when used in other populations.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2021)

Coastal flood risk within a peri-urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2021)

Geochemistry of deep Tunguska Basin sills, Siberian Traps: correlations and potential implications for the end-Permian environmental crisis - S. Callegaro; H. H. Svensen; E. R. Neumann; A. G. Polozov; D. A. Jerram; F. M. Deegan; S. Planke; O. V. Shiganova; N. A. Ivanova; N. V. Melnikov (Contributions to Mineralogy and Petrology, 2021)
A vast portion of the plumbing system of the Siberian Traps Large Igneous Province (STLIP) is emplaced in the Tunguska Basin, where borehole data reveal ubiquitous and abundant sills with great lateral extension. These intrusions intersect Cambrian–Ordovician evaporite, carbonate and siliciclastic series, and locally coal-bearing Permian host rocks, with a high potential for thermogenic gas generation. Here we present new geochemical data from 71 magmatic and 4 sedimentary rock samples from the Tunguska Basin center and periphery, recovered from 15 deep sills intercepted by boreholes. The studied samples are all low-Ti basalt and basaltic andesites, confirming absence of high-Ti and alkaline STLIP magmatism in the Tunguska Basin. The sills derive from picritic parental melts produced by extensive melting of a mantle source with recycled crustal components below a thinned lithosphere (50–60 km), within the spinel stability field. The mantle source was dominantly peridotitic, with enriched pyroxenitic domains formed by recycled lower crust, in agreement with previous models for the main tholeiitic STLIP phase. Limited amounts (up to 5%) of highly radiogenic granitoids or moderately radiogenic metapelites were assimilated in upper crustal magma reservoirs. After emplacement, sills intruded in Cambrian evaporites assimilated marlstones and interacted with the evaporitic host rocks, probably via fluids and brines. This is the first time that such process is described in subvolcanic rocks from all across the volcanic basin. The sills are correlated geochemically with the established chemostratigraphy for the on-craton STLIP lava piles and intrusions (Norilsk region). Sills correlated with the Morongovsky–Mokulaevsky Fm. and the Norilsk-type intrusions are the most voluminous, present all across the central Tunguska Basin, and bear the strongest evidence of interaction with evaporites. Massive discharge of thermogenic volatiles is suggested by explosive pipes and hydrothermal vent structures throughout the Tunguska Basin. We propose that this voluminous pulse of magmatism is a good candidate for the hitherto unidentified early intrusive phase of the STLIP, and may link the deep Tunguska basin sills to the end-Permian environmental crisis.

The place beyond the trees: renewed excavations of the Middle Stone Age deposits at Olieboomspoort in the Waterberg Mountains of the South African Savanna Biome - A. Val; P. de la Peña; M. Duval; S. Bansal; F. Colino; J. Culey; T. Hodgskiss; P. Morrissey; A. Murray; M. Murungi; F.H. Neumann; K. Shadrach; et al. (Archaeological and Anthropological Sciences, 2021)
Olieboomspoort is one of the few rock shelters in the vast interior of southern Africa documenting pulses of occupation from the Acheulean until the end of the Later Stone Age. Revil Mason excavated the site in 1954 and attributed the large Middle Stone Age (MSA) lithic assemblage to his middle phase of the so-called Pietersburg Industry. Recent work at the site has focused on the Holocene layers, but little is known about the earlier phases of shelter use. Here, we provide some background to the shelter, give a history of past research and present initial results following renewed fieldwork at the site. The MSA deposits contain abundant lithic artefacts and ochre, and we present an initial description of these cultural remains. Palynological analysis reveals limited potential for palaeoenvironmental reconstructions, but some faunal remains indicate open grasslands. We dated two equid teeth that provided highly consistent combined U-series-ESR estimates, resulting in a mean age of 150 ± 14 ka (1σ). Even when considering potential sources of uncertainty such as variations in water-intake, these fossils can securely be dated to Marine Isotopic Stage 6. Our reappraisal of site formation processes highlights the fact that the archaeological assemblage is strongly time-averaged. We discuss these different results in the context of a recently rekindled interest in the so-called Pietersburg Industry.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Habitats and fish communities at mesophotic depths in the Mexican Pacific - Jordan A. Hollarsmith; Georgina Ramírez‐Ortiz; Tallulah Winquist; Manuel Velasco‐Lozano; Katherine DuBois; Héctor Reyes‐Bonilla; Kyle C. Neumann; Edwin D. Grosholz (Journal of Biogeography, 2020)
Aim Mesophotic ecosystems, found at the limit of light penetration in the ocean, are rich in biodiversity and harbour unique ecological communities. However, they remain among the least studied habitat zones on earth due to the high costs and technological limitations. Here, we characterize mesophotic communities in two marine reserves across a range of habitat types, depths and temperatures using submersible technologies, with the goal of understanding the processes that structure these communities across biogeographical regions. Location The Bay of La Paz and the Revillagigedo Archipelago, Mexico. Taxa Fish and algal species. Methods We used a small and inexpensive remotely operated vehicle (ROV) to conduct roving‐swim surveys of major habitat types in depths from 12 to 94 m. With the resulting binary data on the presence of fish species, we used generalized linear mixed models and canonical correspondence analysis to determine whether biogenic habitat, depth and/or temperature best explained species richness and community structure across reef and non‐reef substrate. Results We identified 72 species or genera, including new depth records for nine fish species and a new geographical record for one fish species. Our surveys included large undocumented rhodolith beds (free‐living coralline algae) and mesophotic algal communities, in addition to diverse communities of soft corals and sponges. Fish species richness was positively associated with rocky substrate and warmer water, and reef fish communities differed significantly by depth, temperature and biogenic habitat. Main conclusion Our results highlight the importance of biogenic habitat in structuring communities across gradients of depth and temperature. We also demonstrate the effectiveness of a small and economical ROV for conducting mesophotic surveys in remote regions. Our methods and results provide a framework that can be used to greatly increase the biogeographical and taxonomic scope of mesophotic research, especially for readily identifiable taxa such as fish.

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Brain neuropeptide S: via GPCR activation to a powerful neuromodulator of socio-emotional behaviors - Thomas Grund; Inga D. Neumann (Cell and Tissue Research, 2019)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Patients’ Trust in Physician, Patient Enablement, and Health-Related Quality of Life During Colon Cancer Treatment - Nicole Ernstmann; Markus Wirtz; Anika Nitzsche; Sophie E. Gross; Lena Ansmann; Tristan D. Gloede; Julia Jung; Holger Pfaff; Walter Baumann; Stephan Schmitz; Melanie Neumann (Journal of Cancer Education, 2017)

Digital and real-habitat modeling of Hipparchia statilinus based on hyper spectral remote sensing data - L. Luft; C. Neumann; S. Itzerott; A. Lausch; D. Doktor; M. Freude; N. Blaum; F. Jeltsch (International Journal of Environmental Science and Technology, 2016)

Benefits of greenhouse gas mitigation on the supply, management, and use of water resources in the United States - K. Strzepek; J. Neumann; J. Smith; J. Martinich; B. Boehlert; M. Hejazi; J. Henderson; C. Wobus; R. Jones; K. Calvin; D. Johnson; E. Monier; et al. (Climatic Change, 2015)

Improving cross-sectoral climate change adaptation for coastal settlements: insights from South East Queensland, Australia - S. Serrao-Neumann; F. Crick; B. Harman; M. Sano; O. Sahin; R. van Staden; G. Schuch; S. Baum; D. Low Choy (Regional Environmental Change, 2014)

Animal models of social avoidance and social fear - Iulia Toth; Inga D. Neumann (Cell and Tissue Research, 2013)

The production and turnover of extramatrical mycelium of ectomycorrhizal fungi in forest soils: role in carbon cycling - A. Ekblad; H. Wallander; D. L. Godbold; C. Cruz; D. Johnson; P. Baldrian; R. G. Björk; D. Epron; B. Kieliszewska-Rokicka; R. Kjøller; H. Kraigher; E. Matzner; et al. (Plant and Soil, 2013)

Performance of a novel microarray multiplex PCR for the detection of 23 respiratory pathogens (SYMP-ARI study) - S. Bierbaum; N. Königsfeld; N. Besazza; K. Blessing; G. Rücker; U. Kontny; R. Berner; M. Schumacher; J. Forster; V. Falcone; C. Sand; A. Essig; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Central administration of oxytocin receptor ligands affects cued fear extinction in rats and mice in a timepoint-dependent manner - Iulia Toth; Inga D. Neumann; David A. Slattery (Psychopharmacology, 2012)

Orbit determination of the Lunar Reconnaissance Orbiter - Erwan Mazarico; D. D. Rowlands; G. A. Neumann; D. E. Smith; M. H. Torrence; F. G. Lemoine; M. T. Zuber (Journal of Geodesy, 2012)

Bridging the Gap between GPCR Activation and Behaviour: Oxytocin and Prolactin Signalling in the Hypothalamus - Erwin H. van den Burg; Inga D. Neumann (Journal of Molecular Neuroscience, 2011)

Geodetic constraints from multi-beam laser altimeter crossovers - Erwan Mazarico; G. A. Neumann; D. D. Rowlands; D. E. Smith (Journal of Geodesy, 2010)

Vorgaben für Rettung und Brandschutz für die Vortriebe des Koralmtunnels - G. Harer; S. Hubmann; E. Kaiser; D. Lauffer-Neumann (BHM Berg- und Hüttenmännische Monatshefte, 2010)

Potential host shift of the small hive beetle (Aethina tumida) to bumblebee colonies (Bombus impatiens) - D. Hoffmann; J. S. Pettis; P. Neumann (Insectes Sociaux, 2008)

Human bocavirus DNA detected by quantitative real-time PCR in two children hospitalized for lower respiratory tract infection - T. Schenk; B. Huck; J. Forster; R. Berner; D. Neumann-Haefelin; V. Falcone (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Zaba: a novel miniature transposable element present in genomes of legume plants - J. Macas; P. Neumann; D. Požárková (Molecular Genetics and Genomics, 2003)

Lateral migrations of fishes between floodplain lakes and their drainage channels at the Lower Rhine: diel and seasonal aspects - J. Borcherding; M. Bauerfeld; D. Hintzen; D. Neumann (Journal of Fish Biology, 2002)
Although the total migratory activity of fishes from floodplain lakes in the Lower Rhine (Germany) into the connected drainage channels, estimated using electrofishing, fyke nets and visual observations, was low during summer 1997, conspicuous diel migrations of adult bream Abramis brama in June and July were recorded in one of the channels studied. A considerable proportion of the population of the floodplain lake immigrated into the channel at dusk and left it at dawn. During two winters (1994–1995, 1997–1998) the abundance of fishes increased considerably in the channels. The winter migrations, studied in detail in one of the channels in 1997–1998, started in late October, when the water temperature dropped below 10° C. In contrast to the mean of 500 fishes per 100 m channel length between May and October, >5000 fishes were found from November to March, with maximum values of >50 000 fishes per 100 m channel length in February 1998. More than 90% of these shoals were 0+ year fishes, dominated by roach Rutilus rutilus , bream, perch Perca fluviatilis and rudd Scardinius erythrophthalmus . These shoals entered the channel at sunrise and left it around sunset. Generally, the 0+ year fishes in the shoals swam separately from the older fishes, and different reactions towards the attack of predatory fishes were observed. The migrating shoals of juvenile fishes during the winter were interpreted as a strategy to minimize predation risk.

A novel mechanism of silicon uptake - D. Neumann; C. De Figueiredo (Protoplasma, 2002)

Recommendations for the categorization of germ cell mutagens - I.-D. Adler; U. Andrae; P. Kreis; H.-G. Neumann; R. Thier; D. Wild (International Archives of Occupational and Environmental Health, 2000)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

Sulfate reduction in surface sediments of the southeast Atlantic continental margin between 15°38'S and 27°57'S (Angola and Namibia) - Timothy G. Ferdelman; Henrik Fossing; Kirsten Neumann; Horst D. Schulz (Limnology and Oceanography, 1999)
Sulfate reduction rates in the surface sediments from 17 stations from an along‐slope transect (1,300 m) and from a cross‐slope transect (855–4,766 m) were determined in the continental margin sediments of the Benguela Upwelling system. Profiles at all sites in the upwelling area showed increasing sulfate reduction rates from near zero at the surface to a peak at 2–5 cm (up to 29 nmol cm −3 d −1 ) and then decreasing exponentially with depth to near background rates at 10–20 cm depth ( −3 d −1 ). Depth‐integrated sulfate reduction rates were greatest at 1,300 m and decreased exponentially with water depth. Along the transect following the 1,300‐m isobath, depth‐integrated sulfate reduction rates were highest in the north Cape Basin (1.16 +/− 0.23 mmol m −2 d −1 ), decreased over the Walvis Ridge (0.67 +/− 0.02 mmol m −2 d −1 ), and were lowest in the south Angola Basin (0.31 +/− 0.23 mmol m −2 d −1 ). Depth‐integrated sulfate reduction rates were consistent with the known pattern of coastal upwelling intensities and were also strongly correlated with surface organic carbon concentrations. Sulfate reduction rates, both as a function of depth and in comparison with sediment trap data, indicated that lateral downslope transport of organic carbon occurs. Sulfate reduction was estimated to account for 20–90% of the published rates of total oxygen consumption for the sediments at 1,300 m depth and 3–16% of sediments from 2,000 to 3,000 m depth. Comparison of the sulfate reduction rate profiles with the published diffusive oxygen uptake rates showed that the kinetics of oxygen utilization in the surface sediments are much faster than those for anaerobic organic carbon remineralization, although the underlying cause of the difference was not clear.

The Bereznjakovskoje gold trend, southern Urals, Russia - B. Lehmann; J. Heinhorst; U. Hein; M. Neumann; J. D. Weisser; V. Fedesejev (Mineralium Deposita, 1999)

Effects of climatic variability on the annual carbon sequestration by a boreal aspen forest - W. J. Chen; T. A. Black; P. C. Yang; A. G. Barr; H. H. Neumann; Z. Nesic; P. D. Blanken; M. D. Novak; J. Eley; R. J. Ketler; R. Cuenca (Global Change Biology, 1999)
To evaluate the carbon budget of a boreal deciduous forest, we measured CO 2 fluxes using the eddy covariance technique above an old aspen (OA) forest in Prince Albert National Park, Saskatchewan, Canada, in 1994 and 1996 as part of the Boreal Ecosystem‐Atmosphere Study (BOREAS). We found that the OA forest is a strong carbon sink sequestering 200 ± 30 and 130 ± 30 g C m –2 y –1 in 1994 and 1996, respectively. These measurements were 16–45% lower than an inventory result that the mean carbon increment was about 240 g C m –2 y –1 between 1919 and 1994, mainly due to the advanced age of the stand at the time of eddy covariance measurements. Assuming these rates to be representative of Canadian boreal deciduous forests (area ≈ 3 × 10 5 km 2 ), it is likely they can sequester 40–60 Tg C y –1 , which is 2–3% of the missing global carbon sink. The difference in carbon sequestration by the OA forest between 1994 and 1996 was mainly caused by the difference in leaf emergence date. The monthly mean air temperature during March–May 1994, was 4.8 °C higher than in 1996, resulting in leaf emergence being 18–24 days earlier in 1994 than 1996. The warm spring and early leaf emergence in 1994 enabled the aspen forest to exploit the long days and high solar irradiance of mid‐to‐late spring. In contrast, the 1996 OA growing season included only 32 days before the summer solstice. The earlier leaf emergence in 1994 resulted 16% more absorbed photosynthetically active radiation and a 90 g C m –2 y –1 increase in photosynthesis than 1996. The concomitant increase in respiration in the warmer year (1994) was only 20 g C m –2 y –1 . These results show that an important control on carbon sequestration by boreal deciduous forests is spring temperature, via the influence of air temperature on the timing of leaf emergence.

Turbulent Flux Measurements Above and Below the Overstory of a Boreal Aspen Forest - P.D. Blanken; T. A. Black; H. H. Neumann; G. Den Hartog; P. C. Yang; Z. Nesic; R. Staebler; W. Chen; M. D. Novak (Boundary-Layer Meteorology, 1998)

Growth and reproductive cycle of the zebra mussel in the River Rhine as studied in a river bypass - B. Jantz; D. Neumann (Oecologia, 1998)

Sensitivity of Brown Trout Alevins ( Salmo trutta L.) to Nitrite at Different Chloride Concentrations - F. Bartlett; D. Neumann (Bulletin of Environmental Contamination and Toxicology, 1998)

Timing of eclosion in marine insects on Mediterranean shores - studies on Clunio mediterraneus , C. ponticus and Thalassomyia frauenfeldi (Diptera: Chironomidae) - D. Neumann; R. Kaminsky; F. Heimbach (Marine Biology, 1997)

Colonization of adrenal glands and ovaries of mice by variants of HSV 1 and 2 - H. Wiegand; H. P. Dienes; P. Schirmacher; J. Podlech; K. Bohl; M. Bohle; D. Neumann-Haefelin; D. Falke (Archives of Virology, 1991)

Structural analysis of proviral DNA in simian foamy virus (LK-3)-infected cells - M. Schweizer; R. Renne; D. Neumann-Haefelin (Archives of Virology, 1989)

Heterogeneity of primate foamy virus genomes - M. Schweizer; Brigitte Corsten; D. Neumann-Haefelin (Archives of Virology, 1988)

Estimation of exposure of man to substances reacting covalently with macromolecules - P. B. Farmer; H. -G. Neumann; D. Henschler (Archives of Toxicology, 1987)

Malate dismutation by Desulfovibrio - J. D. A. Miller; P. M. Neumann; Lynette Elford; D. S. Wakerley (Archives of Microbiology, 1970)